Twelve previously healthy non‐geriatric dogs present for acute kidney injury after general anaesthesia for non‐emergency surgical procedures in the UK. (20th March 2020) - Rogers‐Smith, E.; Hammerton, R.; Mathis, A.; Allison, A.; Clark, L.
Abstract : Objectives: To characterise common factors after a suspected increase in the incidence of post‐procedure acute kidney injury in healthy dogs presenting for non‐emergency surgical procedures. Materials and Methods: Retrospective analysis of the medical records of 12 dogs that presented for acute kidney injury after general anaesthesia for non‐emergency surgical procedures. Results: The 12 non‐geriatric dogs re‐presented with acute kidney injury at a median of 4 days after surgery to four different veterinary centres, including three multidisciplinary referral practices in the UK. All dogs in this case series weighed more than 20 kg and had a median age of 17 months. There was no apparent association with breed, type of surgery, duration of anaesthesia, perioperative drug choice or non‐steroidal anti‐inflammatory drug administration. Clinical Significance: Although well‐defined in human medicine, there is very little information regarding the association between general anaesthesia and acute kidney injury in animals. No definitive causal link was found in this case series. Clinicians with similar cases are requested to contact the corresponding author so a more representative incidence rate can be obtained.